Living Football, Navigating Politics: Salah Assad’s Life Story in Post-Colonial and Post-Conflict Algeria - Mahfoud Amara (7236599) (2025)
This paper examines the life and career of Salah Assad, a legendary Algerian footballer renowned for his pivotal role in Algeria’s historic victory over the former West Germany in the 1982 FIFA World Cup. Widely regarded as one of the nation’s greatest players, Assad’s career provides a unique lens to explore the intersections of football, politics, and identity in post-colonial Algeria. This study investigates his professional achievements, political affiliations, and public life to uncover the broader socio-political dynamics that shaped modern Algeria. By situating Assad’s journey within key historical contexts – including the socialist ideals of post-independence, the rise of political Islam, and the socio-economic turbulence of the 1990s – this paper highlights the role of individual agency in navigating structural forces. Assad’s narrative illustrates how football, as a cultural and political phenomenon, has both mirrored and influenced Algerian society. His enduring legacy as a symbol of resilience and national pride offers a nuanced understanding of the relationship between sport and societal transformation, shedding light on the interplay of culture, politics, and identity in Algeria and beyond. Other Information Published in: The International Journal of the History of Sport License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/09523367.2025.2479455